PEMUKIMAN HYVE: KEHIDUPAN KOLEKTIF UNTUK MILENIAL - Rainier Lazar Hadiprodjo; Martin Halim (Jurusan Arsitektur dan Perencanaan, 2021)
The millennial generation has a very wide and large opportunity and opportunity to innovate in this era. Therefore, this millennial generation is a great asset to realize national independence in all aspects. Currently the number is around 30% of the total population of Indonesia and is expected to continue to grow. It is predicted that the millennial generation will find it difficult to own a home in the next few years. Coupled with a pandemic that limits the movement of people. Therefore it is necessary to carry out in-depth research on the space requirements that are very much needed for millennials, so that they can create new parameters for housing specifically for millennials who have flexible and practical preferences.